2001
DOI: 10.1103/physrevlett.86.5015
|View full text |Cite
|
Sign up to set email alerts
|

Isospin Asymmetry in the Pseudospin Dynamical Symmetry

Abstract: Pseudospin symmetry in nuclei is investigated considering the Dirac equation with a Lorentz structured Woods-Saxon potential. The isospin correlation of the energy splittings of pseudospin partners with the nuclear potential parameters is studied. We show that, in an isotopic chain, the pseudospin symmetry is better realized for neutrons than for protons. This behavior comes from balance effects among the central nuclear potential parameters. In general, we found an isospin asymmetry of the nuclear pseudospin … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

10
101
1

Year Published

2002
2002
2016
2016

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 110 publications
(112 citation statements)
references
References 26 publications
(54 reference statements)
10
101
1
Order By: Relevance
“…In Refs. [21,22], it was shown that the observed pseudospin splitting arises from a cancellation of the several energy components, and the PSS in nuclei has a dynamical character. A similar conclusion was reached in Refs.…”
mentioning
confidence: 99%
See 3 more Smart Citations
“…In Refs. [21,22], it was shown that the observed pseudospin splitting arises from a cancellation of the several energy components, and the PSS in nuclei has a dynamical character. A similar conclusion was reached in Refs.…”
mentioning
confidence: 99%
“…(4), it can be seen that the system possesses exact PSS when Σ ′ = 0. Unfortunately, the condition cannot be realized in real nuclei, many efforts are devoted to analyze the contributions of various terms to the PSS [21][22][23][24]. However, as there exist deficiencies mentioned before, we decouple Eq.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Since those terms arise from the coupling of those spinor components in their first-order Dirac equations, they have a non-trivial, i.e., different from identity, matrix structure. Therefore, their suppression amounts to have the upper (spin symmetry) or lower (pseudospin symmetry) spinors satisfying second-order equations of Shrödinger type, i.e, with no matrix structure (see [6][7][8][9][10], and [11] for a brief review). This is possible because we have both scalar and vector potentials S and V .…”
Section: Introductionmentioning
confidence: 99%